Reform of Islamic Family Law in The Arab Republic of Egypt - Ulva Hiliyatur Rosida; Mahmoud Abd Elfattah Ibrahim Essa (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2023)
This paper discusses Islamic family law in Egypt. Type research used is studies literature and use approach qualitative .The Arab Republic of Egypt is commonly known as the State of Egypt. This country is one of the countries in the Islamic world that reforms family law in the form of codification of Islamic family law. Islamic family law in Islamic society in the Arab Republic of Egypt is very interesting to study, because in this Islamic family law, the spirit and soul of the revelation of Allah ta'ala and the sunnah of the Prophet Muhammad exist. The renewal of Islamic family law in the Arab Republic of Egypt is discussed regarding three scopes, namely typology, application, and his goal.This scientific work uses a literature study research method whose data is not obtained from the counting procedure.